Practical Solutions for Qualitative Promotion of National and International Medical Education Events: Experiences of Participating Medical Education Specialists - Samane Babaei; Sara Bagheri; Somaye Sohrabi; Masomeh Kalantarion (Strides in Development of Medical Education)
Dear Editor,Organizing national and international medical education conferences offers an invaluable forum for networking, information sharing, innovation, and transformation in the field of medicine (1)...